Impact of scaling up of kangaroo mother care on neonatal mortality among babies born with birth weight - Tinku Thomas; Arin Kar; Krishnamurthy Jayanna; Prem Mony; Suman P N Rao; Maryann Washington; Prabhu Deva Gowda; Swaroop Narayana; Shashidhar Rao; Mohan Harnahalli Lakkappa (BMJ Public Health)
Objective To assess the impact of scaling up of kangaroo mother care (KMC) on neonatal mortality among babies born with birth weight <2000 g across an entire district in southern India.Design, setting and participants Within an implementation research setting, analysis of a prospective birth cohort of babies with birth weight <2000 g born during March–December 2018 in Koppal district of Karnataka state, India, to estimate the incidence, risk and HRs of neonatal mortality associated with KMC.Intervention Initiation and maintenance of KMC.Outcome measures Neonatal mortality.Results Among 23 667 live births, 1152 (4.9%) had birth weight <2000 g; the birth weight was <1500 g in 24% and <1000 g in 4%. Among them, 213 (18%, 95% CI 16% to 21%) babies died during the neonatal period, with 56% of the mortality occurring in the first 3 days of life and risk of mortality decreasing with higher birth weight. Overall, KMC was initiated in 816 (71%) babies; KMC-initiated babies had a substantially lower risk of neonatal mortality (risk ratio 0.07 (95% CI 0.05 to 0.09)). In a subset of 705 babies ‘eligible-for-KMC’ after exclusion of deaths, referrals or ‘terminal discharges’ (leaving against medical advice) in the first 3 days of life, and whose mother was a resident of the study area, 88% (95% CI 85% to 90%) were initiated on KMC. The RR of mortality among KMC-initiated babies remained low at 0.05 (95% CI 0.03 to 0.08) after adjusting for covariates and propensity-score adjusted analysis to address selection bias. Among 874 babies with follow-up data till 29 days of life, neonatal mortality rate was 24.4% (95% CI 21.6% to 27.3%); it was 6.4% (95% CI 4.7% to 8.6%) among KMC-initiated babies and 74.8% (95% CI 67.8% to 79.1%) among non-initiated babies (n=233).Conclusion KMC implementation across a district was associated with substantial reduction in neonatal mortality. Scaling up KMC coverage across large geographies could facilitate achieving global child survival targets.